Osteocytic FGF23 and Its Kidney Function - Agoro, Rafiou; Ni, Pu; Noonan, Megan L.; White, Kenneth E. (Frontiers in Endocrinology, 2020)
Osteocytes, which represent up to 95% of adult skeletal cells, are deeply embedded in bone. These cells exhibit important interactive abilities with other bone cells such as osteoblasts and osteoclasts to control skeletal formation and resorption. Beyond this local role, osteocytes can also influence the function of distant organs due to the presence of their sophisticated lacunocanalicular system, which connects osteocyte dendrites directly to the vasculature. Through these networks, osteocytes sense changes in circulating metabolites and respond by producing endocrine factors to control homeostasis. One critical function of osteocytes is to respond to increased blood phosphate and 1,25(OH)2 vitamin D (1,25D) by producing fibroblast growth factor-23 (FGF23). FGF23 acts on the kidneys through partner fibroblast growth factor receptors (FGFRs) and the co-receptor Klotho to promote phosphaturia via a downregulation of phosphate transporters, as well as the control of vitamin D metabolizing enzymes to reduce blood 1,25D. In the first part of this review, we will explore the signals involved in the positive and negative regulation of FGF23 in osteocytes. In the second portion, we will bridge bone responses with the review of current knowledge on FGF23 endocrine functions in the kidneys.